The political-economic transformations in central and eastern Europe: A tragic neglect of civil society - Williams, Michael; Reuten, Geert (School of Management Working Papers, 1993)
The events of 1989-92 and the flood of advice from bourgeois economists is critically examined in the light of the Hegelian-Marxist theory of the mixed economy. The, sometimes catastrophic, failures of transition are laid at the door of the neglect of civil society.